2010
DOI: 10.1007/s00024-010-0211-0
|View full text |Cite
|
Sign up to set email alerts
|

Edge Detection and Depth Estimation Using a Tilt Angle Map from Gravity Gradient Data of the Kozaklı-Central Anatolia Region, Turkey

Abstract: In this paper the application of an edge detection technique to gravity data is described. The technique is based on the tilt angle map (TAM) obtained from the first vertical gradient of a gravity anomaly. The zero contours of the tilt angle correspond to the boundaries of geologic discontinuities and are used to detect the linear features in gravity data. I also present that the distance between zero and AEp=4 pairs obtained from the TAM corresponds to the depth to the top of the vertical contact model. Alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(59 citation statements)
references
References 21 publications
0
49
0
10
Order By: Relevance
“…Directional derivative-based techniques commonly use vertical or horizontal gradients (derivatives) of degree first or second, analytic signal (AS) amplitudes or their various combinations in order to improve the edges, and also to outline the possible boundaries of the gravity and pseudogravity sources (e.g. Balkaya, Göktürkler, Erhan, & Levent, Ekinci, 2012;Blakely & Simpson, 1986;Debeglia & Corpel, 1997;Oruç, 2011Oruç, , 2014Roest, Verhoef, & Pilkington, 1992). Inversion techniques are frequently used to estimate the model parameters whose responses are similar to the measured data, but the wellknown under-determined and non-uniqueness nature of the potential field data makes the processing and interpretation difficult.…”
Section: Yunus Levent Ekinci and Erdinç Yiğitbaşmentioning
confidence: 99%
“…Directional derivative-based techniques commonly use vertical or horizontal gradients (derivatives) of degree first or second, analytic signal (AS) amplitudes or their various combinations in order to improve the edges, and also to outline the possible boundaries of the gravity and pseudogravity sources (e.g. Balkaya, Göktürkler, Erhan, & Levent, Ekinci, 2012;Blakely & Simpson, 1986;Debeglia & Corpel, 1997;Oruç, 2011Oruç, , 2014Roest, Verhoef, & Pilkington, 1992). Inversion techniques are frequently used to estimate the model parameters whose responses are similar to the measured data, but the wellknown under-determined and non-uniqueness nature of the potential field data makes the processing and interpretation difficult.…”
Section: Yunus Levent Ekinci and Erdinç Yiğitbaşmentioning
confidence: 99%
“…The math calculations are based on Fast Fourier Transformation (FFT). The technique is based on the tilt angle of the first vertical gradient of gravity anomaly (Oruc, 2011). The technique was first proposed by Miller and Singh (2003), and developed by Verduzco et al (2004) in order to be used for gridded data, and suggested to be used with the total horizontal derivative of the tilt angle as an edge detector (Oruc, 2011).…”
Section: -D Matlab Gravity Depth Inversionmentioning
confidence: 99%
“…where is the magnetic or gravity field and / , / , and / are the first derivative in x, y, and, z directions. The tilt amplitudes range between − /2 and + /2 which corresponds to a wide dynamic range of amplitudes for sources at different depths (Oruc, 2011). Verduzco et al (2004) stated that the angle is also employed as an automatic-gain-control-filter in order to equalize the results from weak and strong potential field anomalies.…”
Section: -D Matlab Gravity Depth Inversionmentioning
confidence: 99%
See 1 more Smart Citation
“…Por lo tanto la DE confirma los resultados de la AI, bajo el supuesto de que los bordes de las fuentes anómalas son causadas por contactos verticales. Esta correlación es una manera de confirmar la ubicación horizontal y la profundidad de bordes que reflejan diferentes atributos de características lineales, tales como fallas, contactos, bordes de cuencas y levantamientos (Oruç, 2011). La configuración de la gravimetría terrestre (Figura 6B) muestra que el sistema dominante es el NW-SE, así como el N-S y en menor medida el NE-SW, evidenciando que en la parte central del mapa, y en la porción oriental el valor de cero del AI junto con la Deconvolución de Euler tiene una coincidencia adecuada, asociadas a posibles fallas.…”
Section: Lineamientos Geofísicosunclassified